Evaluation of Central Nervous System Infections in Medicolegal Autopsies - Karayel, Ferah; Pakiş, Işıl; Sav, Aydın; Turan, Arzu Akçay; Çetin, Gürsel (The Bulletin of Legal Medicine, 2004)
The aim of our retrospective study is to present the histopathological features of central nervous system infections 103 central nervous system infections determined at autopsies, performed in Forensic Medicine Council from 1998 to 2002 were analysed. Cases were classified according to age, gender, microscopic features of brain infection and the cause of death. Microscopically, cases were classified as encephalitis and meningitis. Also brain abcesses and serebritis were evaluated. In 50,4% of our cases the cause of death was natural, and 49,6% were classified as trauma complications. 85 were (83,3%) male and 18 (16,6%) were female. Microscopically we found meningitis at 73 cases (70,87%), 60 (58,25%) of them were bacterial in origin, 8 cases (%7,76%) were lymphocytic, 5 cases (4,85%) were chronic granulomatous meningitis. One nocardia and 4 tuberculosis meningitis were found in chronic granulomatous meningitis group. 19 cases of encephalitis (18,44%) were found. Five cases (4,85%) were diagnosed as encephalitis due to Rabies, 1 case (0,97%) as HIV encephalitis, 1 case (0,97%) as PMLE, 4 cases (3,88%) as Prion disease and 3 cases (2,91%) had meningoencephalitis. Eight cases (7,76%) were classified as NOS encephalitis since any étiologie agent could be isolated. One of the 6 cases (5,82%) diagnosed as brain abcesses was mycotic. 2 cases (1,94%) with nonsuppurative serebritis were found. Pathology of the central nervous system infections is very complex and overlapping. In conclusion, it needs a multidiscip-lianary laboratory investigations in the pathology of infections diseases.Key words: Central nervous system infection, autopsy
Keywords: central nervous system infection; autopsy